Diagnosis and treatment of cardiac angiosarcoma - Aleksandra Ołownia; Jakub Orczyk; Agata Tokarzewska; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2023)
Primary cardiac tumors are very rare in the population. About 20% of it are malignant. The most common type of cardiac malignant tumor is angiosarcoma. This tumor has the ability to infiltrate surrounding tissues and form distant metastases. Angiosarcoma is most often located in the right atrium and it mostly attacks men. This neoplasm is difficult to diagnose, because it has no specific symptoms. Patients with this tumor may complain of a chest pain, cardiac arrhythmias, suffocation and distal oedema. The rarity of occurrence and the lack of specyfic symptoms contribute to late diagnosis of the disease and worse prognosis of patients. Angiosarcoma can also be misdiagnosed as pneumonia or more common cardiovascular disease for example coronary artery disease. In advanced stage, this tumor can even lead to myocardial rupture. Various imaging methods are used in the diagnostics of this neoplasm for example: CT, MRI, PET-CT or Echocardiography. Histopathological examinations are less frequently used due to the risk of serious complications like hemothorax. Due to the very uncommon occurrence of the angiosarcoma, guidelines describing treatment of patients with this neoplasm, have not been developed yet. Currently, surgical removal of the tumor (if it is possible), chemiotherapy and radiotherapy are used. Reaserches on the genetic mutations which cause angiosarcoma and the development of appropriate drugs may give patients a chance for more effective treatment in the future